Clinical evidence in the phenomenon of Alien Abduction - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
Purpose: Starting from the classic definition of "alien abduction", the present research, starting from the study published in 2020 on the proposed clinical classification of this particular phenomenon, is aimed at confirming the theoretical assumption of psychopathological origin.  Methods: Clinical interview, based on narrative-anamnestic and documentary evidence and the basis of the Perrotta Human Emotions Model (PHEM) concerning their emotional and perceptual-reactive experience, and administration of the battery of psychometric tests published in international scientific journals by the author of this work: 1) Perrotta Integrative Clinical Interviews (PICI-2), to investigate functional and dysfunctional personality traits; 2) Perrotta Individual Sexual Matrix Questionnaire (PSM-Q), to investigate the individual sexual matrix; 3) Perrotta Affective Dependence Questionnaire (PAD-Q), to investigate the profiles of affective and relational dependence; 4) Perrotta Human Defense Mechanisms Questionnaire (PDM-Q), to investigate the defence mechanisms of the Ego.  Results: Preliminary results from the interviews and the anamnestic form would suggest that the phenomenon of alien abductions has a greater tendency to occur in the female group, in the adult and mature group (and tends to diminish but not disappear with advancing age) and in the group geographically originating in central-northern Italy (due to lower religious influences but greater openness to the typical contents of ufological and mystery narratives). Moreover, the subsequent results would lead us to deduce with almost total certainty, concerning the selected sample, that the phenomenon of alien abductions has an absolute prevalence in the believing population concerning the existence of paranormal phenomena per se, even in the absence of objective and/or scientific evidence. It is a phenomenon that is almost completely linked (110/112, 98.2%) to a medium-low or not fully educated cultural level. Based on the PICI-2 it emerged that the primary emerging disorder is alternatively the delusional disorder, the dissociative disorder and the narcissistic disorder; followed, as secondary disorders, by the delusional disorder (if it is not considered as primary disorder), the schizoid disorder, the borderline disorder, the obsessive disorder and the psychopathic disorder. The analysis of functional traits also reported the marked dysfunctional tendency of the classes referring to self-control, sensitivity, Ego-Es comparison, emotionality, ego stability, security and relational functionality, confirming here too the marked dysfunctional tendency of the clinical population. According to the PSM-Q, almost 2/3 of the participants (73/112, 65.2%) present a dysfunctional tendency to sexual behaviour and a marked tendency to chronicle feelings of shame in avoidance behaviour or hyposexuality. Furthermore, 100% of the sample of the population surveyed report having suffered significant or serious psychological or physical abuse at a young age, or intra-parental relational imbalances, or in any case a sexual upbringing that was not open and lacking in free communication. According to the PDM-Q, 27.7% (31/112) are affected by affective dependency, with greater emphasis on types I (neurotic), VI (covert narcissist), V (borderline) and III (histrionic), in that order of descent. Finally, the PDM-Q reveals the widespread psychopathological tendency of the functional ego framework for the mechanisms of isolation, denial, regression, reactive formation, denial, projection, removal, withdrawal, instinct, repression and idealisation. Conclusion: This research confirms the psychopathological nature of the alien abduction phenomenon, which deserves to be treated using a psychotherapeutic approach (preferably cognitive-behavioural and/or strategic) and possibly also pharmacological in serious cases, depending on the symptoms manifested and the severity of the morbid condition.